Distribution and Relationships Regarding Fe, Al Oxides, and Microorganisms in Soil Microaggregates of Chinese Fir Plantation - Huang Rongzhen; Wang Jinping; Zhu Liqin; Huang Guomin; Shen Sijia; Li Yanyan; Wan Hongyu; Wu Haoze (Shuitu baochi tongbao)
[Objective] The distribution of Fe, Al oxides, and microbial community diversity in red soil microaggregates, and their relationships were studied in order to provide a theoretical basis for the improvement of subtropical red soil structure. [Methods] This study was conducted on a chinese fir plantation, which is the typical plant stand in the subtropical red soil region. The contents of Fe, Al oxides, bonded organic matter, and microbial communities of different soil microaggregate grain sizes in different soil layers (topsoil, 0—10 cm; middle soil, 10—20 cm; subsoil, 20—30 cm) were measured. Their relationships were analyzed by the redundancy analysis method (RDA). [Results] Different forms of Fe, Al oxide contents in soil micro-aggregates were present in the following order: dithionite-citrate-bicarbonate-extractable oxides (Fed, Ald) ≫acid ammonium oxalate-extractable oxides (Feo, Alo) > sodium pyrophosphate-extractable oxides (Fep, Alp). In general, Fe and Al oxide contents increased slowly with decreasing soil micro-aggregate grain sizes. The Fep and Ald contents decreased slowly with increasing soil depth, and Alp content in the subsoil was far greater than in the topsoil. The main microorganisms in the chinese fir plantation soil were bacteria, and gram-positive and negative bacteria. The effect of micro-aggregate grain size on microorganisms was greater in topsoil than in middle soil and subsoil. The phospholipid fatty acids (PLFAs) of microorganisms in soil micro-aggregates of 50—200 μm diameter were greater than in micro-aggregates of other diameters. The richness, Shannon index, and Simpson index of microorganisms were greatest in topsoil, and the richness and Shannon index of microorganisms were greatest in soil micro-aggregates with the lowest diameter. RDA revealed that antino bacteria PLFAs, gram-positive bacteria PLFAs, and microbial Shannon and Simpson indexes were highly significantly and negatively correlated with Fed. Bacteria PLFAs showed highly significant positive relationships with Ald and Alo contents. Fungus, bacteria, gram-negative bacteria, arbuscular mycorrhizal fungus PLFAs showed negative relationships with Fe-Al bonded organic carbon 〔Fe(Al)-SOC〕 content. [Conclusion] The distributions of Fe, Al oxides, and microbial community diversity in subtropical red soil micro-aggregates were affected by soil layers and micro-aggregate size. Different types of microorganisms were affected by different forms of Fe and Al oxides, and bonded organic carbon.